Gamified experimental physics classes: A promising active learning methodology for higher education - Forndran, Freerik; Zacharias, Carlos Renato [UNESP] (IOP Publishing, 2019)
Gamification is defined as the use of game design elements in a non-game context. In higher education, gamification is a methodology intending to motivate students to acquire academical knowledge and soft skills, while keeping them engaged and pleased with the learning process. This study reports the application of a gamified class concerning electric resistors, the first of a 12-topic discipline offered to 2nd-year students in physics and engineering. Adopting a Flipped Classroom methodology and a narrative based on household power consumption, traditional contents about resistors and electricity were taught. Also, instructions about how to use an ohm-meter and how to configure an electronic spreadsheet to do basic statistics were given. In order to customize and enrich the class, some optional contents (usually in a video) were made available. The access to the experimental activities was constrained by approval in four graded quizzes. Every activity was acknowledged by virtual coins to be converted in benefits (extra time to run final examinations, permission to consult class appointments and the opportunity to re-discuss a mistake in the final examination) and points, to rank students (leaderboard). Forty-five students attended the gamified class. No control group was implemented because this study aimed to find a good design for a gamified class, not to compare traditional to active methodologies. The overall student acceptance was excellent, and they reported that gamification can be a more engaging methodology than traditional classes, further developing soft skills and academic knowledge. However, the time spent to run the gamified class must be arranged, reducing the time inside the classroom. The opportunity to perform the experiment was considered essential, and could not be substituted by videos or texts since new doubts and concerns are pointed out during the practice when the teacher is present. Gamification can be a methodology capable of engaging and being enjoyable students, giving them more than just information but also soft skills.
Keywords: Active learning; gamification; physics; STEM